The Pitch Lake, Trinidad, B.W.I. - (:unkn) unknown (Yuille's Printerie Ltd., 2010)
This is a picture showing the expanse of the pitch lake at La Brea, once considered to be the 8th wonder of the world and largest natural deposit of emulsified asphalt. The depressions in the lake are full of rainwater and ponds have formed. On the horizon there is a single story building on the left and various trees on the right.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Asphalt industry--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--La Brea; Pitch; Ponds--Trinidad and Tobago; [1910]; Pitch Lake, The (La Brea)